DLIC1, but not DLIC2, is upregulated in colon cancer and this contributes to proliferative overgrowth and migratory characteristics of cancer cells - Even, Ipek; Reidenbach, Sonja; Hofmann, Ilse (The FEBS journal, 2019)
Cytoplasmic dynein-1 is a large minus-end-directed microtubule motor complex involved in membrane trafficking, organelle positioning, and microtubule organization. The roles of dynein light intermediate chains (DLICs; DLIC1 and DLIC2) within the complex are, however, still largely undefined. In this study, we investigated the possible roles of DLICs in epithelial homeostasis and colon cancer development. Mutant clonal analysis of Drosophila Dlic in the follicular epithelium of Drosophila ovary showed defects in nuclear positioning, epithelial integrity, and apical cell polarity. Consistently, knockdown of human DLIC1 and DLIC2 in colon carcinoma cells resulted in damaged epithelial organization, disturbed lumen formation, and impaired apical polarity establishment in three-dimensional cell culture. Depletion of DLIC1 and DLIC2 led to reduced proliferation, enhanced apoptosis rates, disrupted mitotic spindle assembly, and induction of G2/M arrest in cell cycle progression. Moreover, reduced levels of DLIC1 in contrast to DLIC2 impaired the migratory ability. On the other hand, immunohistochemical examination of human colorectal tissue samples and further colorectal cancer dataset analysis showed a significant upregulation for DLIC1 in tumors, whereas DLIC2 expression was unchanged. In addition, the overexpression of DLIC1 caused increased proliferation, decreased apoptosis and enhanced migration, whereas DLIC2 overexpression did not result in any significant changes. Together, these results indicate that DLIC1 and DLIC2 contribute to the establishment and maintenance of epithelial homeostasis. Furthermore, these findings present the first evidence that DLIC1 and DLIC2 have distinct roles in colon cancer development and that DLIC1 may contribute to proliferative overgrowth and migratory characteristics.
Gesehen am 18.09.2019